Human-Robot Interaction for Remote Application - Achmad, M. S. Hendriyawan; Priyandoko, Gigih; Mohd Razali, Daud; Hamzah, Ahmad (2016)
The development of Human-Robot interaction needs an advanced knowledge when the robot performs complex tasks. Traditionally, the interaction between human and robot tends to be operated with a peer to peer mode which relies on dedicated and customized network protocol. Our innovation emphasizes the use of robot operating system (ROS) which runs the distributed network concept and provides the solution to prevent re-invention the wheel in the robotic software development to interact with a human in the dynamic configuration. This innovation is highly recommended in the large scale robot development, i.e., industrial applications or military missions.